β-Propeller blades as ancestral peptides in protein evolution. - Klaus O Kopec (Public Library of Science (PLoS), 2013)
Proteins of the β-propeller fold are ubiquitous in nature and widely used as structural scaffolds for ligand binding and enzymatic activity. This fold comprises between four and twelve four-stranded β-meanders, the so called blades that are arranged circularly around a central funnel-shaped pore. Despite the large size range of β-propellers, their blades frequently show sequence similarity indicative of a common ancestry and it has been proposed that the majority of β-propellers arose divergently by amplification and diversification of an ancestral blade. Given the structural versatility of β-propellers and the hypothesis that the first folded proteins evolved from a simpler set of peptides, we investigated whether this blade may have given rise to other folds as well. Using sequence comparisons, we identified proteins of four other folds as potential homologs of β-propellers: the luminal domain of inositol-requiring enzyme 1 (IRE1-LD), type II β-prisms, β-pinwheels, and WW domains. Because, with increasing evolutionary distance and decreasing sequence length, the statistical significance of sequence comparisons becomes progressively harder to distinguish from the background of convergent similarities, we complemented our analyses with a new method that evaluates possible homology based on the correlation between sequence and structure similarity. Our results indicate a homologous relationship of IRE1-LD and type II β-prisms with β-propellers, and an analogous one for β-pinwheels and WW domains. Whereas IRE1-LD most likely originated by fold-changing mutations from a fully formed PQQ motif β-propeller, type II β-prisms originated by amplification and differentiation of a single blade, possibly also of the PQQ type. We conclude that both β-propellers and type II β-prisms arose by independent amplification of a blade-sized fragment, which represents a remnant of an ancient peptide world.